Dijkstra Algorithm Implementation in Determining the Shortest Route of Industrial Gas Distribution in PT Tira Austenite Tbk Cikarang with Python Programming Language - Bernadetha Nathalia Fitra Soverenty; Cyrenia Novella Krisnamurti (Universitas Sanata Dharma, 2022)
Mathematics is used in various fields of human life, one of them is in the industrial field. In the field of industrial mathematics can be used in finding the shortest route in distributing industrial gas. Finding the shortest route was done using Dijkstra's algorithm and developing the Python programming language. The purpose of this study is to determine the shortest route on industrial gas distribution at PT Tira Austenite Tbk Cikarang using the Python programming language. This type of research is applied research. The results obtained from this study are the Python programming language that can be used to find the shortest route of industrial gas distribution and users only enter the starting point and endpoint data on the program.